Oral Candidiasis: Aiding in the Diagnosis of HIV-A Case Report - Arvind Shetti; Ishita Gupta; Shivyogi M. Charantimath (Hindawi Limited, 2011)
Opportunistic fungal infections account for a significant amount of morbidity associated with HIV disease. Candidiasis is the most common oral opportunistic infection affecting people with HIV infection or AIDS. It is considered as an important marker of immune suppression and may be the initial manifestation of the disease in about 10% of HIV-infected adults. We report a case of an apparently healthy 45-year-old male with oral candidiasis which proved to be the first indicator of HIV infection.